Strengthening Historical Awareness through the Utilization of Primary Archives of the Jogja Library Center: A Transformative Approach - Pandji Saputra; Roro Wilis; Aman; Naufal Raffi Arrazaq (Universitas Hamzanwadi, 2026)
This study aims to analyze the use of primary archives from the Jogja Library Center collection, integrated with the historical inquiry model as a representation of a transformative learning approach, and its implications for students' historical awareness, particularly in the New Order to Reformation materials. The study used a mixed-method approach with an embedded design strategy, involving a history teacher and 25 12th-grade students of SMA Negeri 9 Yogyakarta selected through purposive sampling. Data were collected through semi-structured interviews, participant observation, and a Likert questionnaire, which were then analyzed using descriptive-quantitative and interactive qualitative methods using the Miles and Huberman model. The results showed that using contemporary newspapers as primary sources during the historical inquiry stage encouraged students to engage in critical reflection, deconstruct single narratives, and understand the multi-perspective nature of history. Student responses to this learning program were very positive, with an average score of 4.20–4.80 and an agreement level of 72–100%. The study concluded that integrating primary archives with the historical inquiry model effectively increased students' critical-genetic historical awareness, although the degree of internalization of the transformation varied between individuals.